A review of the validity of malnutrition screening tools used in older adults in community and healthcare settings – A MaNuEL study. (April 2018) - Power, Lauren; Mullally, Deirdre; Gibney, Eileen R.; Clarke, Michelle; Visser, Marjolein; Volkert, Dorothee; Bardon, Laura; de van der Schueren, Marian A.E.; Corish, Clare A.
Summary: Background: Older adults are at increased risk of malnutrition compared to their younger counterparts. Malnutrition screening should be conducted using a valid malnutrition screening tool. An aim of the Healthy Diet for a Healthy Life (HDHL) Joint Programming Initiative (JPI) 'Malnutrition in the Elderly Knowledge Hub' (MaNuEL) was to review the reported validity of existing malnutrition screening tools used in older adults. Methods: A literature search was conducted to identify validation studies of malnutrition screening tools in older populations in community, rehabilitation, residential care and hospital settings. A database of screening tools was created containing information on how each tool was validated. Results: Seventy-four articles containing 119 validation studies of 34 malnutrition screening tools used in older adults were identified across the settings. Twenty-three of these tools were designed for older adults. Sensitivity and specificity ranged from 6 to 100% and 12–100% respectively. Seventeen different reference standards were used in criterion validation studies. Acceptable reference standards were used in 68 studies; 38 compared the tool against the Mini Nutritional Assessment-Full Form (MNA-FF), 16 used clinical assessment by a nutrition-trained professional and 14 used the Subjective Global Assessment (SGA). Twenty-five studies used inappropriate reference standards. Predictive validity was measured in 14 studies and was weak across all settings. Conclusions: Validation results differed significantly between tools, and also between studies using the same tool in different settings. Many studies have not been appropriately conducted, leaving the true validity of some tools unclear. Certain tools appear to be more valid for use in specific settings.